Characterization of the dysplastic Walch type C glenoid. (August 2018) - Paul, R.; Knowles, N.; Chaoui, J.; Gauci, M-O.; Ferreira, L.; Walch, G.; Athwal, G. S.
Abstract : Aims: The Walch Type C dysplastic glenoid is characterized by excessive retroversion. This anatomical study describes its morphology. Patients and Methods: A total of 29 shoulders with a dysplastic glenoid were analyzed. CT was used to measure retroversion, inclination, height, width, radius-of-curvature, surface area, depth, subluxation of the humeral head and the Goutallier classification of fatty infiltration. The severity of dysplasia and deficiency of the posterior rim of the glenoid were recorded. Results: A type C glenoid occurred in 1.8% of shoulders referred to our tertiary centres. The mean retroversion, inclination, height, width, radius-of-curvature, surface area, and depth of the glenoid were 37°, 3°, 46 mm, 30 mm, 37°, 1284 mm 3, and 16 mm, respectively. The mean posterior subluxation was 90%. The Goutallier class was < 2 in 25 shoulders (86%). Glenoid dysplasia was mild in four, moderate in 14, and severe in 11 shoulders. The typical appearance of the posterior glenoid rim had a rounded or 'lazy J' morphology. The glenoid neck was deficient in 18 shoulders (62%). Conclusion: A dysplastic Type C glenoid characteristically has a uniconcave retroverted morphology, a deficient posteroinferior rim and scapular neck, and a reduced depth. These findings help to define the unique anatomical variations and may aid the planning of surgery and the development of components for these patients. Cite this article: Bone Joint J 2018;100-B:1074–9.